KEDUDUKAN QANUN BIDANG SUMBERDAYA ALAM DALAM SISTEM HUKUM NASIONAL - Efendi Idris (Jurnal Dinamika Hukum, 2014)
The whole of the qanun of natural resources in Aceh is enacted based on the competence of its enactment granted by some nation laws. Therefore, the position of it in terms of natural resources in nation legal system is equal to other regional laws that is as a rule in running regional autonomy as an implementing law from the nigher rule. Thus, in the enactment must follow the principles of qanun enactment as a part of national legal system. Keywords: qanun existence, natural resources, legal system